Female labor force participation in developing countries - Sher Verick (IZA World of Labor, 2014)
While womenâs labor force participation tends to increase with economic development, the relationship is not straightforward or consistent at the country level. There is considerably more variation across developing countries in labor force participation by women than by men. This variation is driven by a wide variety of economic and social factors, which include economic growth, education, and social norms. Looking more broadly at improving womenâs access to quality employment, a critical policy area is enhancing womenâs educational attainment beyond secondary schooling.
Keywords: J16; J21; J22; O11; O12; 330; female labor force participation; developing countries; employment